2018
DOI: 10.1029/2018wr022619
|View full text |Cite
|
Sign up to set email alerts
|

The Added Value of Assimilating Remotely Sensed Soil Moisture for Estimating Summertime Soil Moisture‐Air Temperature Coupling Strength

Abstract: To date, the direct use of remote‐sensing soil moisture data sets for examining surface/atmosphere coupling strengths has been hampered by the presence of significant random errors and data gaps in these products. This study investigates the potential for obtaining an improved observation‐based lower bound of summertime soil moisture‐air temperature coupling strength via the assimilation of long‐term, remote‐sensing soil moisture data sets into a simple, prognostic model driven by observed rainfall. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Figure 2a further illustrates that the L4 product demonstrates much higher levels of skill relative to the OL simulation in areas of low rain gauge density (i.e., areas with large distances to the nearest rain gauge in Figure 2d), such as central Australia, and in regions where CPCU data are not used to derive the L4 and OL products, including Africa and the high latitudes (Reichle et al, 2017a). Hence, assimilating satellite-based Tb is associated with a relatively larger increase in soil moisture skill (Dong & Crow, 2018b;Liu et al, 2018;Reichle et al, 2008a). Due to the sparsity of rain gauge observations in these regions, the OL simulation contains elevated levels of random error.…”
Section: Global L4 Versus Ol Performance Analysismentioning
confidence: 98%
See 3 more Smart Citations
“…Figure 2a further illustrates that the L4 product demonstrates much higher levels of skill relative to the OL simulation in areas of low rain gauge density (i.e., areas with large distances to the nearest rain gauge in Figure 2d), such as central Australia, and in regions where CPCU data are not used to derive the L4 and OL products, including Africa and the high latitudes (Reichle et al, 2017a). Hence, assimilating satellite-based Tb is associated with a relatively larger increase in soil moisture skill (Dong & Crow, 2018b;Liu et al, 2018;Reichle et al, 2008a). Due to the sparsity of rain gauge observations in these regions, the OL simulation contains elevated levels of random error.…”
Section: Global L4 Versus Ol Performance Analysismentioning
confidence: 98%
“…Following previous soil moisture error analyses (e.g., Dong & Crow, 2018b;Dorigo et al, 2010), we assume that SMAP L4 ( L4 ) anomalies are linearly related to the unknown true soil moisture anomaly ( ):…”
Section: Relative Skill Of Smap L4 and Ol Versus True Soil Moisturementioning
confidence: 99%
See 2 more Smart Citations
“…The changes of large-scale atmospheric circulations may be the main cause of temperature anomalies, and small-scale physical processes of local energy balance such as soil moisture-atmosphere coupling could also make a contribution to them [5]. Many studies have shown that soil moisture anomalies play an important role in soil moisture-temperature coupling [6,7], as it could control the energy budget by the partitioning of latent heat flux and sensible heat flux, further impacting the air temperature [8,9]. When soil moisture decreases, less water can be used for evapotranspiration, resulting in a decrease of latent heat flux [8,10].…”
Section: Introductionmentioning
confidence: 99%